Fabrication of thin flm silicon / PEDOT : PSS hybrid devices - Tay, Tian Yu (2016)
There has been much interest and demand in the area of renewable energy sources as of late, and solar photovoltaics is a highly viable option given that the sun’s energy incident on the surface of the earth is able to provide 10 000 times that of our global energy annual consumption. One major obstacle to the use of this abundant yet clean energy is the high cost associated with the fabrication and maintenance of the solar photovoltaic devices. Therefore in this project the objective is to combine the low cost fabrication process of an organic device using PEDOT: PSS with that of a high efficiency inorganic device using silicon material. To further reduce the cost, thin – film silicon of thickness 40μm will be used. Five Thin – Film Planar Silicon / PEDOT: PSS device were fabricated in this project with the highest recorded efficiency at 5.0521%. The process of fabricating a Thin – Film Planar Silicon / PEDOT: PSS hybrid device and to further optimize this efficiency, through studying the various parameters such as, thickness of the Silicon material, doping concentration the bulk and surface carrier lifetimes through simulations was carried out. It was also found through these simulations that this Thin Film Planar Silicon / PEDOT: PSS hybrid device is capable of efficiencies higher than 10%, therefore there are improvements to the process that have been analyzed and recommended for future work.